Inovasi Beton Berbasis Lingkungan Menggunakan Abu Kayu Sengon Albasia Sebagai Subsitusi Parsial Semen Terhadap Kuat Tekan Beton - Heny Hidayati, Sri; Irsyadi Firdaus, Muhammad; Eko Wicaksono, Anton; Satria Romanasta, Ahmad (Jurnal Teknik Sipil, 2025)
The use of sengon albasia ash waste as a partial cement substitute in concrete production is carried out to reduce combustion waste and also reduce cement use. This study focuses on the use of sengon albasia wood ash waste. The use of sengon albasia wood ash as a cement substitute causes a significant decrease in the slump test value. The use of sengon albasia wood ash as a partial cement substitute in concrete mixes actually produces different results depending on the proportion. If added as much as 10%, the concrete's compressive strength actually increases, but if it reaches 20% or 30%, the compressive strength actually decreases. This occurs because this type of wood ash has a significant water absorption capacity. As a result, the water that should be used for The chemical activity occurring between cement and water is diminished, so that the bond between the cement mixture as a binder and aggregate as a filler is reduced, and ultimately the concrete's compressive strength also decreases.